ENPP1抑制剂和调节免疫反应的方法 (2025)
本申请提供了用于抑制ENPP1的化合物、组合物和方法。主题方法的方面包括将样品与ENPP1抑制剂化合物接触以抑制ENPP1的cGAMP水解活性。在一些情况下，该ENPP1抑制剂化合物是细胞不可渗透的。ENPP1抑制剂化合物可以在细胞外发挥作用，阻断cGAMP的降解。还提供了用于治疗癌症的药物组合物和方法。该方法的方面包括向受试者给药治疗有效量的ENPP1抑制剂以治疗受试者的癌症。在某些情况下，该癌症是实体瘤癌症。还提供了向受试者施用放射疗法联合向受试者给药ENPP1抑制剂的方法。该放射疗法可以在主题方法中以有效降低对受试者造成的放射损伤，但是仍然能激发免疫响应的剂量和/或频率来施用。 Compounds, compositions and methods are provided for the inhibition of ENPP1. Aspects of the subject methods include contacting a sample with an ENPP1 inhibitor compound to inhibit the cGAMP hydrolysis activity of ENPP1. In some cases, the ENPP1 inhibitor compound is cell impermeable. ENPP1 inhibitor compounds can act extracellularly to block the degradation of cGAMP. Also provided are pharmaceutical compositions and methods for treating cancer. Aspects of the methods include administering to a subject a therapeutically effective amount of an ENPP1 inhibitor to treat the subject for cancer. In certain cases, the cancer is a solid tumor cancer. Also provided are methods of administering radiation therapy to a subject in